Factors associated with adolescent participation in out-of-school physical activity - Jiménez Boraita, Raúl; Arriscado Alsina, Daniel; Gargallo Ibort, Esther; Dalmau Torres, Josep María (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Participation in out-of-school physical activities contributes to the fulfilment of physical activity recommendations in adolescents and may have a direct influence on health. The aim of the study was to analyse the performance of extracurricular physical sports activities, assessing their relationship with various lifestyle habits and physical and psychosocial health indicators, as well as the influence of different socio-demographic variables. The study was carried out on a sample of 761 students (14.51 ± 1.63 years) from 25 educational centers. Performance of extracurricular physical sports activities, Physical activity engagement, hours of nightly sleep, adherence to the Mediterranean diet, maximum oxygen uptake, body mass index, health-related quality of life, self-esteem, satisfaction with body image were assessed and various sociodemographic factors. Being younger, being a boy, having a high socioeconomic level, having been born in Spain, residing in urban environments and being satisfied with body image were predictors of performing extracurricular physical sports activities. These factors accounted for 19.2% of physical sports participation. Likewise, adolescents who practiced these activities had lower rates of overweight / obesity and higher values ​​of adherence to the Mediterranean diet, physical activity, health-related quality of life, self-esteem and maximum oxygen uptake. The practice of out-of-school physical activity is influenced by multiple factors that should be taken into account for its promotion.